Analysis of Beaches and Beach Managing in Context of New Maritime Domain and Sea Ports Act - Kovačić, Mirjana; Favro, Srećko (Transactions on Maritime Science, 2024)
Beaches are a resource that often captures public interest, especially in local communities, due to the various roles they play in people's lives. Interest in beaches is continuous and diverse, while the pressure on them is increasing. Economic interest, as a result of tourist demand, is evident both globally and in Croatia. Simultaneously, there is a growing interest in beaches among the experts and scientists, considering various issues, including the economic impacts on beaches and their effects on the environment. Although various laws and directives regulate the management and protection of beaches as a resource, the approaches vary. In 2023, the Croatian Parliament amended a new Maritime Domain and Sea Ports Act (MDSPA), which introduces different approaches to beaches beyond their classification. The subject of this research is beaches in general, and open questions in the new legal framework. The purpose of the research is to analyse the institutional framework and how beaches are managed in Croatia. The authors analyse the new legal solutions in MDSPA, explaining the jurisdiction, form of using and managing, protection, and the economic use of beaches. The aim of the research is to analyse the theoretical and legal aspects of beaches, identify open questions, propose methodology and measures to improve the beach managing model in Croatia.